MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA DENGAN MENGGUNAKAN PEMBELAJARAN HYBRID DI SEKOLAH DASAR - Sastra Wijaya; Iva Sarifah; Nurjannah Nurjannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Transformation in the field of education can be carried out by developing more innovative and creative learning designs through a student-centered learning approach. The use of technology as a learning medium is the right choice for teachers to improve the mathematical literacy skills of elementary school students, the combination of face-to-face learning with technology-based learning is then called hybrid learning. The mathematical literacy indicators used in this study refer to questions formulated in PISA organized by the OECD. Based on this, this study then aims to determine the effect of hybrid learning in improving students' mathematical literacy skills. The results showed that the average score of students after using this learning was 80.60 with a standard deviation of 14.505 and a maximum score of 100. As for the results of the effectiveness test on the results of the independent sample t-test, it showed significant results with the calculation results of F = 0.083, df = 80, sig (2-tailed) = 0.002, which successfully answers the research hypothesis of the normality test using the Kolmogorov Smirnov test states that the data value score Sig.0.002 ≤ 0.05, thus it can be ascertained that there is a significant effect of hybrid learning on students' literacy skills.